Is there an alternative to floating exchange rates? - Olaf Sievert (Intereconomics, 1986)
The discussion about the international monetary system has revived in recent months. Has the changeover to floating exchange rates in 1973 not fulfilled the expectations it aroused? How should the present proposals for the reform of exchange rate policy be assessed?
Keywords: 330; Exchange Rate Policy